Body mass index, weight change and survival in non-Hodgkin lymphoma patients in Connecticut women - Han, Xuesong (Nutr Cancer, 2013)
BACKGROUND: Evidence is emerging that obesity and weight gain may affect the prognosis of several types of cancer. We investigated the impact of body mass index (BMI) as well as pre- and post-diagnosis weight changes on non-Hodgkin lymphoma (NHL) prognosis. METHODS: A cohort of 573 female incident NHL cases diagnosed during 1996–2000 in Connecticut was followed for a median of 7.8 years. Self-reported height and weight at three time points before and after diagnosis were collected. Hazard ratios (HR) and 95% confidence intervals (CI) were estimated using proportional hazard models adjusting for factors believed to be associated with overall survival of NHL. RESULTS: Underweight (BMI < 18.5; HR = 2.84; 95% CI = 1.12–7.15) before diagnosis was associated with poorer survival compared to being normal weight (18.5 <= BMI < 25). Pre-diagnosis weight loss (HR = 1.42; 95% CI = 1.02–1.97) and post-treatment weight loss (HR = 1.98; 95% CI = 1.14–3.45) and weight gain (HR = 1.85; 95% CI = 1.04–3.32) were associated with poorer survival. CONCLUSION: NHL patients who were underweight, lost weight pre-diagnosis, or change weight after treatment were found to have a poorer survival.